Thrombus Histology as It Relates to Mechanical Thrombectomy: A Meta-Analysis and Systematic Review - Bhambri, Ankur; Adapa, Arjun Rohit; Liu, Yang; Boeckh-Behrens, Tobias; Procházka, Václav; Hernández-Fernández, Francisco; Barbella-Aponte, Rosa Angélica; Hashimoto, Tetsuya; Savastano, Luis E; Gemmete, Joseph J; Chaudhary, Neeraj; Shih, Albert J; et al. (Neurosurgery, 2021)
BACKGROUND: Appropriate thrombus-device interaction is critical for recanalization. Histology can serve as a proxy for mechanical properties, and thus inform technique selection. OBJECTIVE: To investigate the value of histologic characterization, we conducted a systematic review and meta-analysis on the relationship between thrombus histology and recanalization, technique, etiology, procedural efficiency, and imaging findings. METHODS: In this meta-analysis, we identified studies published between March 2010 and March 2020 reporting findings related to the histologic composition of thrombi in large vessel occlusion stroke. Studies with at least 10 patients who underwent mechanical thrombectomy using stent retriever or aspiration were considered. Only studies in which retrieved thrombi were histologically processed were included. Patient-level data were requested when data could not be directly extracted. The primary outcome assessed was the relationship between thrombus histology and angiographic outcome. RESULTS: A total of 22 studies encompassing 1623 patients met inclusion criteria. Clots associated with good angiographic outcome had higher red blood cell (RBC) content (mean difference [MD] 9.60%, 95% CI 3.85-15.34, P = .008). Thrombi retrieved by aspiration had less fibrin (MD -11.39, 95% CI -22.50 to -0.27, P = .046) than stent-retrieved thrombi. Fibrin/platelet-rich clots were associated with longer procedure times (MD 13.20, 95% CI 1.30-25.10, P = .037). Hyperdense artery sign was associated with higher RBC content (MD 14.17%, 95% CI 3.07-25.27, P = .027). No relationship was found between composition and etiology. CONCLUSION: RBC-rich thrombi were associated with better recanalization outcomes and shorter procedure times, suggesting that preinterventional compositional characterization may yield important prognostic and therapeutic guidance.
Keywords: Histology; stenty; ischemie mozku; Brain Ischemia; Humans; Clot; Stroke; Systematic review; Meta-analysis; Thrombus; výsledek terapie; Arterial Occlusive Diseases; lidé; arteriální okluzní nemoci; Thrombosis; Stent; Thrombectomy; cévní mozková příhoda; trombektomie; Stents; Treatment Outcome; trombóza; Large vessel occlusion; Ischemic stroke